The Psychometric Properties of the Iranian Version of Repetitive Behavior Scale‐Revised (RBS‐R) Questionnaire in Children With Autism Spectrum Disorder - Amir Mohammad Salehi; Shayan Bahadivand Chegini; Fatemeh Esmaeili; Niloofar Rabiei; Ensiyeh Jenabi; Mohammad Rezaei (Health Science Reports)
ABSTRACT Background and Aims Restricted and repetitive behaviors (RRBs) are fundamental characteristics of autism spectrum disorders (ASD). There is a need for a reliable and valid instrument to evaluate the diversity of RRBs and assess their severity. The Repetitive Behavior Scale‐Revised (RBS‐R) is a recognized tool for screening RRBs. This study aims to investigate the psychometric properties of the RBS‐R questionnaire in Iran by identifying children with ASD who have Persian‐speaking parents. Methods In this case–control study conducted in 2024 in Hamadan, 160 children were included: A case group diagnosed with autism (25 girls, 52 boys) and a control group of healthy volunteer children (30 girls, 53 boys) aged 4–12 years. The ASD group exhibited a minimum mean length of utterance (MLU) of 2. Participants diagnosed with intellectual disabilities were excluded from the study. The study assessed the reliability, content validity, and face validity to evaluate the psychometric properties of the tool. Exploratory factor analysis was used to identify questionnaire subscales. All assumptions, including the Kaiser–Meyer–Olkin (KMO) test, Bartlett's test, and question correlations, were checked. Subscales were extracted using ordinary least squares (OLS) and Equamax rotation, with the number of subscales determined based on the Scree plot method and eigenvalues greater than 1. Results The study identified six factors (aggressive, focused and self‐harming, resistant to change, obsessive, ritualistic, and insistent), which together explained 51.082% of the total variance. The Cronbach's alpha value for the Persian version of RBS‐R was reported as 0.924. The questionnaire showed a sensitivity of 88.31%, specificity of 83.13%, positive predictive value of 82.93%, negative predictive value of 88.46%, and an area under the curve of 91.7%. The selected cutoff value in this study was determined to be 17.5. Conclusion The Persian version of the RBS‐R is valid and reliable. It also demonstrated acceptable internal consistency and sensitivity, suggesting that it can be used as a screening measure for ASD in Iran.